Mapping Research on Factors Associated with the Incidence of Diabetes Mellitus: A Bibliometric Analysis Using VOSviewer - Arlinda Claudina; Gipta Gali Widodo (GLOBAL HEALTH SCIENCE GROUP, 2026)
Diabetes mellitus is one of the most serious non-communicable diseases affecting communities worldwide. The disease is closely associated with unhealthy lifestyle behaviors. This study aimed to analyze and visualize the research landscape on factors associated with the incidence of diabetes mellitus published between 2021 and 2025 using bibliometric analysis with Publish or Perish and VOSviewer. This study utilized Google Scholar data published between 2021 and 2025 and conducted a bibliometric analysis using the Publish or Perish and VOSviewer applications. The search yielded 200 publications, all of which met the inclusion criteria and were included in the bibliometric analysis. The bibliometric analysis of factors associated with the incidence of diabetes mellitus over the past four years identified eleven major research clusters. The highest number of publications was recorded in 2023 and 2025, with 94 articles (47%), followed by 2024 with 42 articles (21%), 2022 with 35 articles (17.5%), and 2021 with 29 articles (14.5%). Publications related to factors associated with the incidence of diabetes mellitus indexed in Google Scholar increased by the end of 2025, indicating sustained research interest in this topic. The most frequently investigated variables in recent years include obesity, white sugar consumption, and family history.